2017
DOI: 10.1002/elsc.201600241
|View full text |Cite
|
Sign up to set email alerts
|

Silybum marianum cell cultures stably transformed with Vitis vinifera stilbene synthase accumulate t‐resveratrol in the extracellular medium after elicitation with methyl jasmonate or methylated β‐cyclodextrins

Abstract: Silybum marianum cell cultures stably transformed with Vitis vinifera stilbene synthase accumulate t-resveratrol in the extracellular medium after elicitation with methyl jasmonate or methylated β-cyclodextrinsThe growing demand for t-resveratrol for industrial uses has generated considerable interest in its production. Heterologous resveratrol production in plant cell suspensions, apart from requiring the introduction of only one or two genes, has the advantage of high biomass yield and a short cultivation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 48 publications
(58 reference statements)
0
29
0
Order By: Relevance
“…Elicitation of the engineered HR with 50 mM MBCD and 100 µM of MeJA significantly increased the release of t -R and its derivatives t -Pn and t -Pt to the liquid medium, whereas piceid remained mainly inside the roots. In contrast, the positive effects of the combined elicitor treatment (MBCD + MeJA) on the t -R production has been previously reported in non-transgenic and transgenic grapevine cell cultures 14 , 60 , and also in transgenic S. marianum cell cultures carrying the VvSTS gene and supplemented with MBCD 17 . The ineffectiveness of elicitation in the HR culture system to improve the total stilbenoid contents was perhaps due to the fast metabolization of stilbenoids in the culture medium, as reported previously 15 , and an increased bioconversion of t -R into the more bioactive derivatives, t -Pn and t -Pt.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Elicitation of the engineered HR with 50 mM MBCD and 100 µM of MeJA significantly increased the release of t -R and its derivatives t -Pn and t -Pt to the liquid medium, whereas piceid remained mainly inside the roots. In contrast, the positive effects of the combined elicitor treatment (MBCD + MeJA) on the t -R production has been previously reported in non-transgenic and transgenic grapevine cell cultures 14 , 60 , and also in transgenic S. marianum cell cultures carrying the VvSTS gene and supplemented with MBCD 17 . The ineffectiveness of elicitation in the HR culture system to improve the total stilbenoid contents was perhaps due to the fast metabolization of stilbenoids in the culture medium, as reported previously 15 , and an increased bioconversion of t -R into the more bioactive derivatives, t -Pn and t -Pt.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, biotechnological studies have shown that Vitis vinifera cell cultures need elicitation treatments for an efficient t -R production, the best results being achieved by combining methyl jasmonate with the expensive cyclodextrins 16 . Silybum marianum transgenic cell suspensions carrying the V.vinifera stilbene synthase3 ( Vv STS) gene treated only with cyclodextrins have also yielded t -R 17 , as have HR of peanut 18 , 19 and V. rotundifolia 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In this report, production of silymarin was less affected in the transgenic cultures, possibly due to an intrinsic precursor bottleneck from the monolignol branch limits silymarin synthesis. The fact is that overexpressed STS gene will react with the excessively produced precursors of non-bioactive compounds such as coniferyl alcohol, while the metabolic flux toward the silymarin production was kept unchanged, this may provide a route to extend the applications of plant cell cultures for both constitutive and foreign valuable metabolites production (Hidalgo, Martínez-Márquez et al 2017).…”
Section: Plant Suspension Culturementioning
confidence: 99%
“…One example is the stable transformation of Silybum marianum (L.) Gaertn. cell suspension cultures with the Vitis vinifera L. stilbene synthase gene, allowing increased accumulation of t-resveratrol [56]. In addition, overexpression of the neutral / alkaline invertase (NINV) gene in Taxus chinensis (Rehder & E.H.Wilson)…”
Section: Calli and Cell Suspension Culturesmentioning
confidence: 99%